2022
DOI: 10.3389/fpsyt.2022.906796
|View full text |Cite
|
Sign up to set email alerts
|

A computational lens on menopause-associated psychosis

Abstract: Psychotic episodes are debilitating disease states that can cause extreme distress and impair functioning. There are sex differences that drive the onset of these episodes. One difference is that, in addition to a risk period in adolescence and early adulthood, women approaching the menopause transition experience a second period of risk for new-onset psychosis. One leading hypothesis explaining this menopause-associated psychosis (MAP) is that estrogen decline in menopause removes a protective factor against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 143 publications
0
1
0
Order By: Relevance
“…Similarly, another study revealed that postmenopausal women with schizophrenia had significantly lower scores in tests measuring verbal fluency, attention, and working memory than premenopausal women with schizophrenia. These findings suggest menopause could exacerbate cognitive deficits in women with schizophrenia-spectrum disorders [28][29][30][31].…”
Section: Impact Of Menopause On Symptoms Of Schizophrenia-spectrum Di...mentioning
confidence: 99%
“…Similarly, another study revealed that postmenopausal women with schizophrenia had significantly lower scores in tests measuring verbal fluency, attention, and working memory than premenopausal women with schizophrenia. These findings suggest menopause could exacerbate cognitive deficits in women with schizophrenia-spectrum disorders [28][29][30][31].…”
Section: Impact Of Menopause On Symptoms Of Schizophrenia-spectrum Di...mentioning
confidence: 99%